Interference Management Schemes for the Shared Relay Concept. (15th September 2010) - Panah Panah, Ali Y. Ali Y.; Truong Truong, Kien T. Kien T.; Peters Peters, Steven W. Steven W.; Heath Heath, Robert W. Robert W.
Abstract : Sharing a multiantenna relay among several sectors is a simple and cost-effective way to achieving much of the gains of local interference mitigation in cellular networks. Next generation wireless systems, such as ones based on the Third Generation Partnership Projects Long-Term Evolution Advanced, will employ universal frequency reuse to simplify network deployment. This strategy is anticipated to create significant cell-edge interference in the location of the shared relays, thus rendering advanced interference management strategies a necessity. This paper proposes several interference management strategies for the shared relays ranging from simple channel inversion at the relay, to more sophisticated techniques based on channel inversion in combination with partial and full base station coordination in the downlink and uplink. Given that the relay functionality influences total interference, both amplify-and-forward and decode-and-forward type relays are considered throughout. In this context, channel cancelation techniques are investigated for one-way relaying and also the spectrally efficient two-way relaying protocol. Simulations show that strategies based on two-way shared relaying with bidirectional channel inversion at the relay often perform best in terms of total system throughput while one-way techniques are promising when the relay power is low.